Pengaruh Motivasi Konsumen, Persepsi Kualitas DanSikap Konsumen Terhadap Keputusan Pembelian ProdukPonsel Samsung (Studi Kasus Pada Mahasiswa Universitas Muhammadiyah Surakarta) - Anggriani, Aprillia Ragil; , Drs. Farid Wajdi, MM, Ph.D (2017)
This study aims to determine: (1) the influence of the motivation of consumers to purchasing decision of Samsung mobile phones among students at the University of Muhammadiyah Surakarta, (2) the effect of perceived quality on product purchasing decisions of Samsung mobile phones among students at the University of Muhammadiyah Surakarta, (3) the effect of attitude Purchasing decisions of consumers against Samsung mobile phones among students at the University of Muhammadiyah Surakarta. This study included a survey with quantitative approach. The population in this study is that consumers Samsung mobile phone users among students at the University of Muhammadiyah Surakarta, with questionnaires of the 100 respondents. The sampling technique used in this study was convenience sampling, ie where researchers have the freedom to choose anyone, or who happened to meet with researchers who can be sampled as per the requirements of the existing population. Based on calculations determined the number of samples used by 100 respondents. Data analysis method used is validity, reability, normality, multicollinearity, heteroscedasticity, and test multiple linear regression analysis with t-test, F and coefficient of determination (R2). Hypothesis tests showed consumer motivation, perceived quality, and consumer attitudes have a significant impact on product purchasing decisions samsung phones.